2009
DOI: 10.3944/aott.2009.359
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between three irrigation methods in the debridement of contaminated bovine cancellous bone and the effect of duration of irrigation on the efficiency of debridement

Abstract: Our findings showed that the most efficient method of cleansing contaminated bone samples was high-pressure pulsatile lavage and that prolonged irrigations did not enhance the efficiency of the irrigation method; however, high-pressure irrigation of 3 minute duration resulted in the greatest bone damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, other methods are needed to clear debris in the nanometer range. Studies comparing irrigation techniques based on the outcome of debris removal do exist, but the studied contaminants are often too large to compare with soot (rock dust: ≤4 mm 12,13 or construction sand: 0.063-2.0 mm 14,15 ). Interestingly, Dreager et al 12 found that in soft tissue samples contaminated by rock dust, bulb syringe and suction irrigation were more effective in debridement than high-pressure lavage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other methods are needed to clear debris in the nanometer range. Studies comparing irrigation techniques based on the outcome of debris removal do exist, but the studied contaminants are often too large to compare with soot (rock dust: ≤4 mm 12,13 or construction sand: 0.063-2.0 mm 14,15 ). Interestingly, Dreager et al 12 found that in soft tissue samples contaminated by rock dust, bulb syringe and suction irrigation were more effective in debridement than high-pressure lavage.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more importantly, HPPL has also been shown to mitigate the healing response of soft tissues and fractures secondary to the microscopic/macroscopic damage and removal of cellular material that occurs during its use. [17][18][19][20][21][22][23][24][25][26] However, Bhandari et al 27 and Svoboda et al 28 both demonstrated that pulsed high-pressure lavage is more effective than low-pressure lavage or bulb syringe irrigation at removing surface bacteria-particularly in wounds associated with a delay in debridement greater than 3 hours (presumably because of glycocalyx). Similarly, the FLOW 29 investigators found that…”
Section: Effect On the Tissuesmentioning
confidence: 99%
“…Perhaps more importantly, HPPL has also been shown to mitigate the healing response of soft tissues and fractures secondary to the microscopic/macroscopic damage and removal of cellular material that occurs during its use. 17–26…”
Section: Irrigation In Open Fracture Managementmentioning
confidence: 99%